Development of an online system for reporting service problems of state-owned companies. Issue 3 (March 2021) - Cahyana, R; Satria, E; Faujiah, E; Heryanto, D
Abstract: Several state-owned companies in Indonesia provide subscription services for the general public. One of them is the Regional Water Company as a provider of clean water. Handling service problems by the company affect customer satisfaction. This study aims to develop that online system for reporting service problems by following the Rational Unified Process stages, which are limited to the construction stage. The research successfully developed the system, which includes user activation functions, problem maps, as well as reporting and history of problems, and their handling. The system becomes a communication bridge between the company and the customer. Through this system, companies can see the condition of customers displayed in the form of icons and at several points of geographical location on the map. The green icon represents the condition of the customer who is not dealing with the problem, and vice versa is red. The yellow icon represents the condition of the customer whose issue is being handled by the company.